Synthesis of 2-iminothiazolidin-4-ones via copper-catalyzed [2 + 1 + 2] tandem annulation. Issue 4 (12th January 2023) - Zhao, Mingming; Guo, Yiming; Wang, Qi; Liu, Lanqi; Zhang, Shujie; Guo, Wei; Wu, Lin-Ping; Qiu, Fayang G.
Abstract : In this paper, an efficient synthesis of 2-iminothiazolidin-4-ones through a copper-catalyzed tandem annulation reaction of alkyl amines, isothiocyanates and diazo acetates is presented. Abstract : In this paper, an efficient synthesis of 2-iminothiazolidin-4-ones through a copper-catalyzed tandem annulation reaction of alkyl amines, isothiocyanates and diazo acetates is presented. Notable advantages of this [2 + 1 + 2] cyclization methodology include readily accessible starting materials, simple operation, mild reaction conditions, high yields, step-economy and diverse functional group tolerance. In addition, the reaction is applicable to the gram scale synthesis and the preparation of bioactive molecules.